Coumarin Derivatives as Anticancer Agents for Lung Cancer Therapy: A Review - Kumar, Manvendra; Singla, Ramit; Dandriyal, Jyoti; Jaitak, Vikas (Anti-Cancer Agents in Medicinal Chemistry, 2018)
Background: The prevalence of lung cancer is 14% among the newly diagnosed cancer cases worldwide. Currently, the number of drugs that are in clinical practice is having a high prevalence of side effect and multidrug resistance. Researchers have made an attempt to expand a suitable anticancer drug that has no MDR and side effect. Objective: Extensive exploration of Coumarin derivatives as a potent inhibitor of variety of proteins including EGFR, tyrosine kinase, ERK1/2, PI3K, HSP 90, Bax, STAT proteins, NF-ΚB and telomerase which have been associated with lung cancer. Method: The recent literature was surveyed utilizing the online resources and databases including scifinder, pubchem, EMBL, scopus and google scholar. Results: Upon analyzing the structure-activity relationship, it was found that N-aryl carboxamide, phenyl substitution at the C-3 position and 1,2,3- triazolyl, trihydroxystilbene, amino substitution at the C-4 position of the coumarin nucleus were the most effective in targeting lung cancer. Conclusion: This review is a collaborative and extensive compilation of synthetic strategies, mechanism of action, and the structure-activity relationship thereof for the management of lung carcinoma.
Keywords: NSCLC